2019
DOI: 10.7150/jca.28989
|View full text |Cite
|
Sign up to set email alerts
|

A review on the accuracy of bladder cancer detection methods

Abstract: Background and purpose : Bladder cancer is the most common malignant tumour in the urinary system, with a high incidence and recurrence rate. While the incidence of bladder cancer has been rising in recent years, the prevalence of bladder carcinoma is showing an increasing tendency in the younger age group. There are several methods to detect bladder cancer, but different methods have varying degrees of accuracy which intrinsically depends on the method's sensitivity and specificity. Our aim was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
100
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(106 citation statements)
references
References 44 publications
2
100
0
4
Order By: Relevance
“…Characterized by a high incidence and recurrence rate, bladder cancer is considered to be the most common malignant cancer of urinary system [ 15 ]. The current protocol for treatment still fails to overcome this challenge effectively.…”
Section: Discussionmentioning
confidence: 99%
“…Characterized by a high incidence and recurrence rate, bladder cancer is considered to be the most common malignant cancer of urinary system [ 15 ]. The current protocol for treatment still fails to overcome this challenge effectively.…”
Section: Discussionmentioning
confidence: 99%
“…It allows checking for abnormal areas and even to perform transurethral resection of bladder tumor, which can be used to confirm BC diagnosis by deep visualization of the bladder and muscle (if possible) and also serves as the first stage of treatment. However, cystoscopy is a highly invasive examination that can also cause pain and other complications [ 6 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…These biological signals are widely found in both blood and urine. However, urine sample detection is more popular because of its convenience and low-cost, with highest sensitivity and specificity up to 97.2% [29]. Among the biomarkers in the urine sample, bladder tumor antigen (BTA), nuclear matrix protein 22 (NMP22), and fibrin/fibrinogen degradation products (FDP) have been approved by the Food and Drug Administration (FDA) for bladder cancer detection [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Among the biomarkers in the urine sample, bladder tumor antigen (BTA), nuclear matrix protein 22 (NMP22), and fibrin/fibrinogen degradation products (FDP) have been approved by the Food and Drug Administration (FDA) for bladder cancer detection [30,31]. A recent survey showed that BTA in urine with a 56-99% of sensitivity and 72-85.7% of specificity in FDA approved tests, compared with 51-100% and 73-90% in NMP22, respectively [29,32,33]. Arya et al realized the detection of NMP22 and BTA based on ELISA combined with electrochemical method [34], and Geng et al developed a PDMS-based microfluidic chip to detect bladder cancer cells and tumor markers, also NMP22 and BTA, by fluorescence antibody reaction [35].…”
Section: Introductionmentioning
confidence: 99%